Application of NASA-Unified WRF model to carbon dioxide simulation- model development and evaluation. (October 2020) - Tao, Zhining; Kawa, Stephan R.; Jacob, Jossy P.; Liu, David Y.; Collatz, George J.; Wang, James S.; Ott, Lesley E.; Chin, Mian
Abstract: The NASA-Unified Weather Research and Forecasting model has been coupled with the Carnegie-Ames-Stanford Approach biogeochemical model/Global Fire Emissions Database and the Parameterized Chemistry Transport Model (NU-WRF-CASA) to simulate CO2 transport and variability at fine spatial resolutions, which is anticipated to assist in better understanding the mechanisms and processes controlling carbon sources/sinks and in reducing uncertainty in carbon-climate interactions. NU-WRF-CASA is designed to operate in an internally consistent manner in which NASA's Goddard Earth Observing System Model, version 5, can be applied to drive the entire coupled modeling system. A 3-year simulation was carried out for North America to evaluate NU-WRF-CASA's performance under various regions and environmental conditions. Observational CO2 data from tower, flask, aircraft, and satellite measurements were used for model evaluations. The results showed that NU-WRF-CASA correctly distributed CO2 fluxes and reproduced spatial-temporal CO2 transport and variability reasonably well with overall bias within 1 ppmv. Highlights: CASA-GFED terrestrial carbon model has been coupled with NU-WRF to investigate CO2 transport at synoptic scales. The modeling results compare well to CO2  observations for a 3-year simulation covering various environmental conditions. The modeling system offers capability of high-resolution CO2 simulation to support satellite and flight missions.